The secret journeys of Jack London - Golden, Christopher; Lebbon, Tim 1969- (Harper / HarperCollins, 2011)
Seventeen-year-old Jack London makes the arduous journey to the Yukon's gold fields in 1893, becoming increasingly uneasy about supernatural forces in the wilderness that seem to have taken a special interest in him